2014
DOI: 10.2174/1573403x10666140514101748
|View full text |Cite
|
Sign up to set email alerts
|

Interatrial Block in the Modern Era

Abstract: Interatrial block (IAB; P-wave duration ≥ 110 ms), which represents a delay in the conduction between the atria, is a pandemic conduction abnormality that is frequently underappreciated in clinical practice. Despite its comprehensive documentation in the medical literature, it has still not received adequate attention and also not adequately described and discussed in most cardiology textbooks. IAB can be of varying degrees and classified based on the degree of P-duration and its morphology. It can transform i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
69
1
31

Year Published

2015
2015
2021
2021

Publication Types

Select...
5
2
1

Relationship

2
6

Authors

Journals

citations
Cited by 77 publications
(102 citation statements)
references
References 67 publications
1
69
1
31
Order By: Relevance
“…32 In terms of atrial electrophysiology, several P-wave characteristics have been studied for prediction of stroke with well-demonstrated associations in epidemiological studies. 9,12 The initial and terminal portions of the P wave are generally accepted as a reflection of right and left atrial activation, respectively. First, PTFV1 is the product of the depth (μV) of the terminal portion of the P-wave in ECG lead V 1 multiplied by its duration (ms).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…32 In terms of atrial electrophysiology, several P-wave characteristics have been studied for prediction of stroke with well-demonstrated associations in epidemiological studies. 9,12 The initial and terminal portions of the P wave are generally accepted as a reflection of right and left atrial activation, respectively. First, PTFV1 is the product of the depth (μV) of the terminal portion of the P-wave in ECG lead V 1 multiplied by its duration (ms).…”
Section: Discussionmentioning
confidence: 99%
“…[8][9][10] Interestingly, some clinical studies have demonstrated the value of some of these ECG markers for stroke risk stratification. 9,11,12 Of note, patients with atrial abnormalities without evident AF are not placed on oral anticoagulation. 13 Therefore, the identification of such abnormalities may have significant prognostic and therapeutic implications in this setting.…”
mentioning
confidence: 99%
“…Indeed, PTF magnitude ≥0.04 mm•ms, if present along with an interatrial block (P-wave duration >110 ms), is considered highly specific and reasonably sensitive for diagnosing left atrial enlargement. 2 The determination of PTF is restricted to lead V1, wherein lead placement error has a significant potential to result in the misinterpretation of PTF.…”
Section: Letter By Chhabra Et Al Regarding Article "Prevalence and Pmentioning
confidence: 99%
“…2 In particular, authors did not take into consideration the effect of chronic lung disease (especially emphysema) on the PTF. In one of our previous works, we demonstrated that PTF may often be falsely increased in these patients and interpretation of left atrial enlargement in such patients based on PTF alone should be made with caution.…”
Section: Letter By Chhabra Et Al Regarding Article "Prevalence and Pmentioning
confidence: 99%
“…Also, did they use all the 12-leads or mainly lead II for estimating P-wave duration? In all our prior studies, we used a magnifying graticule (10 ×) and used all 12-leads for P-wave measurement which if was not used in the current study may explain a lower prevalence of IAB as noted [2][3][4][5][6][7]. …”
mentioning
confidence: 99%